2013
DOI: 10.1123/japa.21.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Supervised Multimodal Exercise to Reduce Falls Risk in Economically and Educationally Disadvantaged Older Adults

Abstract: Few studies have evaluated the benefit of providing exercise to underprivileged older adults at risk for falls. Economically and educationally disadvantaged older adults with previous falls (mean age 79.06, SD= 4.55) were randomized to four months of multi-modal exercise provided as fully supervised center-based (FS, n =45) or as minim ally supervised home-based (MS, n = 42) or to non-exercise controls (C, n= 32). Comparing groups on the mean change in fall-relevant mobility task performance between baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
0
24
0
6
Order By: Relevance
“…The search returned 4006 records, of which 108 trials involving 23 407 participants were eligible for inclusion (figure 1). 18 The characteristics of the 108 included trials are summarised in online supplementary material B 10 19–125…”
Section: Resultsmentioning
confidence: 99%
“…The search returned 4006 records, of which 108 trials involving 23 407 participants were eligible for inclusion (figure 1). 18 The characteristics of the 108 included trials are summarised in online supplementary material B 10 19–125…”
Section: Resultsmentioning
confidence: 99%
“…However, when considering the primary data, three out of the five studies included in the review reported no differences between SUP and UNSUP interventions (1,19,46). Another included study compared SUP high-intensity training versus an UNSUP low-intensity programme (50); consequently the difference between groups may be attributed to different loading strategies rather than the level of supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Todos los resultados obtenidos en los diferentes artículos son semejantes, corroborándose la relación entre la prevención de caídas y los programas de ejercicio. No obstante, diferentes programas de ejercicio para la prevención de caídas diseñados por numerosos autores, fueron eficaces independientemente de las distintas variables que se pudieron encontrar (Siegrit, 2016;Duque et al 2013;Freiberqer et al 2013;Goble, 2017;Kuptniratsaikul et al 2011;Chang et al 2011;Hyun-oh et al 2012;Almeida et al 2013).…”
Section: Discussionunclassified
“…Del mismo modo es una cuestión prioritaria desarrollar la fuerza muscular que posibilitaría una mejora en la estabilidad postural y por consiguiente una reducción de caídas (Lusa, et al 2012;Zhuang et al 2014;Yu-ning et al 2016;Hyun-Oh et al 2012;Almeida et al 2013).…”
Section: Discussionunclassified